Internal and External Reform of Javanese Language in Deli Javanese Dialect in Binjai City: A Phonological and Lexicon Study - Suprayetno, Edy (Universitas Jambi, Magister Program of English Education Department, 2026)
The Javanese language of the Deli dialect in Binjai City developed in a multilingual situation that brought Javanese speakers together with Indonesian, Deli Malay, and other language elements in everyday communication. This study aims to describe the forms of internal and external renewal of the Javanese language of the Deli dialect in Binjai City, especially in the aspects of phonology and lexicon. The study used a diachronic linguistic approach with a qualitative descriptive method. Data in the form of lingual units showing sound changes, changes in form, and vocabulary replacement were collected through the listening method and the conversation method with the techniques of tapping, noting, recording, fishing, speaking semuka, and vocabularies. Analysis was carried out through the classification of phonological and lexical changes, determination of retention and innovation, and the principles of lexicostatistics and dialectometry. The results showed 39 variants of internal renewal and 26 variants of external renewal. Internal renewal is seen in vowel changes, consonant changes, phoneme additions, phoneme deletions, and changes in form that are not yet fully patterned. External changes primarily occur through lexicon changes resulting from contact with Indonesian, Malay/local languages, English, and product names. These findings confirm that the Deli Javanese dialect in Binjai City retains a number of Javanese characteristics, but also exhibits phonological and lexical adaptations resulting from the social dynamics of the diaspora community.